To what extent are call combinations in chimpanzees comparable to syntax in humans? - Maël Leroux (Revue de Primatologie)
Syntax is considered a key feature distinguishing human language from other non-human animal communication systems. However, evidence for combinatorial capacities in a wide variety of species, such as birds and monkeys, has challenged this assumption. Nevertheless, a contentious debate surrounding the evolutionary origins of syntax remains, specifically whether the combinatorial capacities displayed in animals merely illustrate a case of convergent evolution or whether it could also represent, within the primate lineage, a homologous trait to syntax in humans. In this piece, I review the literature on combinatorial signalling in our closest-living relative, the chimpanzee (Pan troglotytes), central to demonstrating a more ancient evolutionary account of syntax. Specifically, I detail the combinatorial structures highlighted in chimpanzees, the experimental evidence pointing toward the syntactic-like nature of these combinations, as well as the limitations the field needs to overcome to go a step further and address the question of the evolution of syntax more holistically. I discuss future directions building on exciting recent evidence for combinatorial flexibility in chimpanzees and the potential for learning. Finally, by proposing a compositional analysis to documented combinations of gestures with facial expressions, I argue that a promising avenue for the study of the evolution of syntax lies in the understanding of multimodal combinatorial signalling in our closest-living relatives and its ontogeny.